Philosophy of Science in Russia: The St. Petersburg Philosophical Society (1897-1923) - Sinelnikova, Elena (Filozofia Nauki, 2019)
This article is devoted to the philosophy of science in Russia from the end of the 19 th century to the beginning of the 1920s. In that period, the Philosophical Society was one of the philosophy centers in the country. An important characteristic of the society was its interdisciplinarity. This affected both the list of its members and the topics of the papers presented at its meetings. From the very beginning, the society consisted of representatives of various fields of science, including botanists, physicists, mathematicians, lawyers, psychologists, historians, and philosophers. This enabled a comprehensive review of individual philosophical problems and ideas. With the principle of interdisciplinarity at its root, the Philosophical Society became a platform for fruitful debates over important problems from various disciplines, including philosophy of science. Some of them are summarized in this article.